Babyteeth [videorecording (DVD)] - Murphy, Shannon; Scanlen, Eliza, 1999-; Wallace, Toby; Barclay, Emily, 1984-; Kalnejais, Rita (IFC Films, 2020)
A teenage girl with a terminal illness falls in love with a small-time drug dealer and experiences a new lust for life that impacts her parents and those around her.